Estimation of Observer Metameric Failure when Using Modern Displays - A. A. Motyko; N. A. Obukhova; K. A. Smirnov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. The advent of wide-gamut color reproduction devices (LED, laser, or OLED) has exacerbated the problem of color rendering related to individual differences in color perception and referred to as observer metameric failure. Currently, designers of smartphone and TV displays, as well as other playback devices, are aiming to reach a wider gamut; however, there is a lack of device-specific methodologies for assessing the degree of observer metameric failure.Aim. To develop a method for estimating the degree of observer metameric failure. This method can be used to assess the need for a color correction of a particular device in order to compensate for the color rendering problem.Materials and methods. Categorical observers, formed by clustering of color matching functions of individual users, were used. The procedure of searching for pairs of colors that would be indistinguishable for one categorical observer, but would look different for another, i.e., would cause an observer metameric failure, was developed based on the solution of an optimization problem. The decision on the need to implement a color correction for the designed device is made based on the degree of errors on the found pairs of colors for a set of categorical observers.Results. It was shown that modern displays are already associated with the effect of observer metameric failure. Further development of display technologies and an extension of color coverage due to narrowing of spectral characteristics of basic colors will make the problem of observer metameric failure more pronounced, thus requiring special measures of color correction.Conclusion. A method for estimating the degree of observer metameric failure for a particular color reproduction device is proposed. This method can be used to assess the need for implementing color correction measures to compensate for the problem of color rendering by individual users.